Malnutrition in Pediatric with Bronchopneumonia: A Case Report - Nuri Nurhasanah Sugandi; Agustino Rosario Idong; Ayundari Angelia Febriany; Bonifasius Berkah Widodo; Danti Dja Jatnika; Leonardo Diogo; Sharon Felicia Alexandria Manik; Tiodora Arimenda Br Surbakti (Medical Clinical Update, 2023)
Pneumonia is the single largest infectious cause of death in children under five globally andaccounts for one fifth of child deaths. The risk of pneumonia in under-five children is influencedby the nutritional status of the children Malnutrition or undernourishment, particularly ininfants who are not exclusively breastfed, can impair a child's immune system. One million childrendie each year as a result of severe malnutrition, which affects nearly 20 million children worldwide